Institutions and Wage Determination: A Multi-Country Approach - Luca Nunziata (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We present an empirical analysis of the determinants of labour cost in OECD countries, with particular reference to the impact of labour market institutions from 1960 to 1994. The main contribution of the paper is to show that labour market regulations can explain a large part of labour cost rise in OECD countries in the last decades once we control for productivity. These results are consistent with the findings of a companion paper (Nickell et al., 2001) where the effects of institutions on unemployment are examined. The model controls for macroeconomic shocks, and include the possibility of interactions among institutions. We present also a discussion of the potential problems encountered when estimating a macro pooled model like ours. We focus, among other things, on the hypothesis of poolability and on the cointegration properties of the model, suggesting a two way fixed effects specification in GLS form that corrects for heteroskedasticity and serial correlation.The explanatory power of the model is finally tested by means of a series of by country dynamic simulations.
Keywords: 330